A modified halogen-free toughening resin, a preparation method thereof, and a preparation method of a copper-clad plate
Patent Information
- Application Number
- CN202311394542.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-10-26
AI Technical Summary
但环氧树脂也存在脆性大、韧性不足的缺点,并且随着无卤概念的提出和实施后,各种带有阻燃性能的环氧树脂被开发出来
[0028](1)本发明合成的聚酯磷酸酯含有磷酸基团,能与环氧树脂发生环氧反应,将聚酯多元醇加入到环氧树脂网络中,极大的改善了环氧树脂柔韧性差的缺点,并且磷酸基团的加入,燃烧时使聚合物脱水而炭化,从而提高阻燃性;
Smart Images

Figure BDA0004513415940000081
Abstract
Description
Technical Field
[0001] This invention belongs to the field of copper clad laminate technology, specifically relating to a modified halogen-free toughening resin and its preparation method, as well as a method for preparing copper clad laminates. Background Technology
[0002] Epoxy resins possess excellent mechanical properties, bonding ability, chemical stability, ease of processing, and low cost, making them widely used in insulation materials, structural materials, coatings, and adhesives. However, epoxy resins also have drawbacks such as high brittleness and insufficient toughness. Furthermore, with the introduction and implementation of the halogen-free concept, various epoxy resins with flame-retardant properties have been developed.
[0003] Currently, phosphorus-containing epoxy resins are widely used. After removing halogens, these epoxy resins still retain good flame retardant properties, heat resistance, processability, and mechanical properties. However, the addition of phosphorus does not change the brittleness of the epoxy resin and may even affect its flexibility. Therefore, toughening modification is necessary. Summary of the Invention
[0004] To address the shortcomings of the prior art, this invention provides a modified halogen-free toughening resin and its preparation method, as well as a method for preparing copper-clad laminates.
[0005] The first objective of this invention is to provide a modified halogen-free toughening resin comprising, by weight, the following components: 12-18 parts of polyester phosphate ester, 40-55 parts of phosphorus-containing epoxy resin, 15-25 parts of dicyclopentadiene (DCPD) type epoxy resin, 10-15 parts of cyanate ester resin, 6-12 parts of polyphenylene oxide (PPO) resin, 10-18 parts of linear phenolic resin, 0.5-2 parts of curing agent, 0.05-0.2 parts of catalyst, 20-32 parts of filler, and 32-48 parts of solvent.
[0006] Furthermore, the polyester phosphate ester is generated by reacting polyphosphoric acid and polyester polyol at a certain temperature.
[0007] Furthermore, the polyphosphoric acid contains more than 85% P2O5, and the polyester polyol is selected from at least one of polyethylene adipate, 1,6-hexanediol adipate, trimethylolpropane adipate, and diethylene glycol adipate.
[0008] Furthermore, the preparation method of the polyester phosphate ester includes the following steps: under an inert gas atmosphere, 80 to 100 parts of polyester polyol are added first, and 3 to 5 parts of polyphosphoric acid are added while stirring. The temperature is raised to 100 to 110°C and maintained for 3 to 4 hours. Then, after hydrolysis, washing and reflux to remove water, polyester phosphate ester is obtained.
[0009] Furthermore, the phosphorus-containing epoxy resin is selected from one or a mixture of any two or more of the following: DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) type epoxy resin, DOPO-HQ (hydroquinone) type epoxy resin, and DOPO-NQ (naphthoquinone) type epoxy resin.
[0010] Furthermore, the DCPD type epoxy resin is a dicyclopentadiene-phenol epoxy resin.
[0011] Furthermore, the cyanate resin is selected from one or a mixture of any two or more of bisphenol A cyanate, bisphenol F cyanate, diphenylmethane diisocyanate, and dicyclohexylmethane diisocyanate.
[0012] Furthermore, the molecular weight of the polyphenylene ether resin is 1000 to 3000.
[0013] Furthermore, the linear phenolic resin is selected from one or a mixture of any two or more of the following: phenolic resin, bisphenol A resin, dicyclopentadiene resin, and aminotriazine resin.
[0014] Furthermore, the curing agent is selected from one or a mixture of any two or more of dicyandiamide, diaminodiphenylmethane, and diaminodiphenyl sulfone.
[0015] Furthermore, the catalyst is 2-methylimidazole, 2-ethyl-4-methylimidazole, or 2-phenylimidazole.
[0016] Furthermore, the filler is selected from two or more of the following: silica powder, talc powder, SiO2, TiO2, aluminum hydroxide, and aluminum oxide, and the particle size of the filler is 0.5 to 3 μm.
[0017] Furthermore, the solvent is selected from two or a mixture of three of the following: butanone, cyclohexanone, acetone, toluene, and propylene glycol monomethyl ether.
[0018] A second objective of this invention is to provide a method for preparing the above-mentioned modified halogen-free toughening resin, comprising the following steps:
[0019] S1. Dissolve 6-12 parts of polyphenylene ether resin in 16-24 parts of solvent. After the solution is clear, add 10-15 parts of cyanate ester resin. While stirring, heat to 80℃-90℃, add 0.05-0.2 parts of catalyst and react for 0.8-1.2 hours. Stop heating, add another 16-24 parts of solvent, and cool to room temperature to obtain resin 1.
[0020] S2. Take 12-18 parts of polyester phosphate, 40-55 parts of phosphorus-containing epoxy resin, and 15-25 parts of DCPD type epoxy resin. Stir and heat to 80℃-90℃, react for 0.8-1.2h, and then cool to room temperature to obtain resin 2.
[0021] S3. Add resin 1 and resin 2 in sequence, then add 10-18 parts of linear phenolic resin, 0.5-2 parts of curing agent, and 20-32 parts of filler. Stir for 2 hours, and then ball mill for 1 hour to obtain modified halogen-free toughening resin solution.
[0022] Furthermore, the gelation time of the modified halogen-free toughening resin solution obtained in step S3 is 300-400 s.
[0023] The third objective of this invention is to provide a method for preparing a modified halogen-free toughened copper clad laminate, comprising the following steps:
[0024] (1) Preparation of resin solution: Modified halogen-free toughening resin solution was prepared using the method described above.
[0025] (2) Preparation of semi-cured sheet: The modified halogen-free toughening resin liquid prepared in step (1) is transported to the glue applicator, impregnated with electronic grade glass fiber cloth, and baked in an oven at 130-190℃ to produce a semi-cured sheet with a resin content of 40%-60% and a gel time of 60-130s.
[0026] (3) Preparation of copper clad laminate: After stacking two or more prepregs prepared in step (2) according to the required thickness, 18-35μm copper foil is applied to both sides. The modified halogen-free toughened copper clad laminate is prepared by pressing in a vacuum press at a pressure of 0.5-4.5MPa and a temperature gradually increasing from 120℃ to 210℃ for 2-3 hours.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] (1) The polyester phosphate ester synthesized in this invention contains phosphate groups, which can undergo an epoxy reaction with epoxy resin. Adding polyester polyol to the epoxy resin network greatly improves the disadvantage of poor flexibility of epoxy resin. Furthermore, the addition of phosphate groups causes the polymer to dehydrate and carbonize during combustion, thereby improving flame retardancy.
[0029] (2) In this invention, cyanate ester and PPO have good compatibility. Cyanate ester modified with PPO has better heat resistance and dielectric properties, and the toughness of cyanate ester is improved.
[0030] (3) The modified halogen-free toughened copper clad laminate prepared by the present invention has high flexibility, impact strength, peel strength, T288 and glass transition temperature, excellent heat resistance and outstanding flame retardant effect. Detailed Implementation
[0031] The principles and features of the present invention are described below with reference to examples. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. The parts mentioned in the specific embodiments are parts by weight.
[0032] Preparation Example
[0033] The preparation method of polyester phosphate ester includes the following steps:
[0034] Under an inert gas atmosphere, 100 parts of polyester polyol are added first, and 5 parts of polyphosphoric acid are added while stirring. The temperature is raised to 100-110℃ and maintained for 3 hours. Then the temperature is lowered to 25℃, and 5 parts of water are added for hydrolysis for 3 hours to hydrolyze the excess polyphosphoric acid into free phosphoric acid. The free phosphoric acid is then removed by washing with water three times. Finally, the water is removed by reflux to obtain polyester phosphate ester.
[0035] Among them, the polyester polyol is poly(1,6-hexanediol adipate), and the polyphosphoric acid contains more than 85% P2O5.
[0036] Example 1
[0037] A method for preparing a modified halogen-free toughened copper clad laminate includes the following steps:
[0038] (1) Preparation of resin solution:
[0039] S1. Dissolve 6 parts of polyphenylene ether resin in 16 parts of solvent. After the solution is clear, add 10 parts of cyanate ester resin. While stirring, heat to 80℃~90℃, add 0.2 parts of catalyst and react for 1.1h. Stop heating, add another 16 parts of solvent, and cool to room temperature to obtain resin 1.
[0040] S2. Take 12 parts of polyester phosphate, 40 parts of phosphorus-containing epoxy resin, and 15 parts of DCPD type epoxy resin. Stir and heat to 80℃~90℃, react for 1.2h, and then cool to room temperature to obtain resin 2.
[0041] S3. Add resin 1 and resin 2 in sequence, then add 10 parts of linear phenolic resin, 0.5 parts of curing agent and 20 parts of filler, stir for 2 hours, and then ball mill for 1 hour to obtain modified halogen-free toughening resin solution.
[0042] In this process, the polyester phosphate ester was prepared by the preparation example; the phosphorus-containing epoxy resin was a DOPO type epoxy resin; the DCPD type epoxy resin was a dicyclopentadiene-phenol epoxy resin; the cyanate ester resin was diphenylmethane diisocyanate; the molecular weight of the polyphenylene ether resin was 1000-3000; the linear phenolic resin was a bisphenol A type phenolic resin; the curing agent was diaminodiphenyl sulfone; the catalyst was 2-methylimidazole; the filler was 15 parts silica powder and 5 parts talc powder; and the solvent was 10 parts cyclohexanone, 2 parts acetone, and 4 parts propylene glycol monomethyl ether. The gelation time of the modified halogen-free toughening resin solution obtained in step S3 was 349 s.
[0043] (2) Preparation of prepreg:
[0044] The modified halogen-free toughening resin solution prepared in step (1) S3 is conveyed to the glue applicator, impregnated with electronic grade glass fiber cloth, and baked in an oven at 130-190°C to produce a semi-cured sheet with a resin content of 45% and a gel time of 70s.
[0045] (3) Preparation of copper clad laminate:
[0046] After the six semi-cured sheets prepared in step (2) are stacked, 18μm copper foil is applied to both sides. The sheets are then pressed in a vacuum press at a pressure of 0.5-4.5MPa and a temperature that is gradually increased from 120℃ to 210℃ for 2-3 hours to produce a modified halogen-free toughened copper clad laminate.
[0047] Example 2
[0048] A method for preparing a modified halogen-free toughened copper clad laminate includes the following steps:
[0049] (1) Preparation of resin solution:
[0050] S1. Dissolve 8 parts of polyphenylene ether resin in 20 parts of solvent. After the solution is clear, add 13 parts of cyanate ester resin. While stirring, heat to 80℃~90℃, add 0.4 parts of catalyst and react for 1 hour. Stop heating, add another 20 parts of solvent, and cool to room temperature to obtain resin 1.
[0051] S2. Take 15 parts of polyester phosphate, 48 parts of phosphorus-containing epoxy resin, and 20 parts of DCPD type epoxy resin. Stir and heat to 80℃~90℃, react for 1 hour, and then cool to room temperature to obtain resin 2.
[0052] S3. Add resin 1 and resin 2 in sequence, then add 15 parts of linear phenolic resin, 1.2 parts of curing agent and 27 parts of filler, stir for 2 hours, and then ball mill for 1 hour to obtain modified halogen-free toughening resin solution.
[0053] In this process, the polyester phosphate ester was prepared using the preparation example; the phosphorus-containing epoxy resin was DOPO-HQ type epoxy resin; the DCPD type epoxy resin was dicyclopentadiene-phenol epoxy resin; the cyanate ester resin was bisphenol A type cyanate ester; the molecular weight of the polyphenylene ether resin was 1000-3000; the linear phenolic resin was phenolic type phenolic resin; the curing agent was dicyandiamide; the catalyst was 2-methylimidazole; the filler was 17 parts silica powder and 10 parts talc powder; and the solvent was 6 parts butanone, 3 parts acetone, and 11 parts propylene glycol monomethyl ether. The gelation time of the modified halogen-free toughening resin solution obtained in step S3 was 364 s.
[0054] (2) Preparation of prepreg:
[0055] The modified halogen-free toughening resin solution prepared in step (1) S3 is conveyed to the glue applicator, impregnated with electronic grade glass fiber cloth, and baked in an oven at 130-190°C to produce a semi-cured sheet with a resin content of 52% and a gel time of 100s.
[0056] (3) Preparation of copper clad laminate:
[0057] After the six semi-cured sheets prepared in step (2) are stacked, 18-35 μm copper foil is applied to both sides. The sheets are then pressed in a vacuum press at a pressure of 0.5-4.5 MPa and a temperature that is gradually increased from 120°C to 210°C for 2-3 hours to produce a modified halogen-free toughened copper clad laminate.
[0058] Example 3
[0059] A method for preparing a modified halogen-free toughened copper clad laminate includes the following steps:
[0060] (1) Preparation of resin solution:
[0061] S1. Dissolve 12 parts of polyphenylene ether resin in 24 parts of solvent. After the solution is clear, add 15 parts of cyanate ester resin. While stirring, heat to 80℃~90℃, add 0.6 parts of catalyst and react for 0.8h. Stop heating, add another 24 parts of solvent, and cool to room temperature to obtain resin 1.
[0062] S2. Take 18 parts of polyester phosphate, 55 parts of phosphorus-containing epoxy resin, and 25 parts of DCPD type epoxy resin. Stir and heat to 80℃~90℃, react for 0.8h, and then cool to room temperature to obtain resin 2.
[0063] S3. Add resin 1 and resin 2 in sequence, then add 18 parts of linear phenolic resin, 2 parts of curing agent and 32 parts of filler, stir for 2 hours, and then ball mill for 1 hour to obtain modified halogen-free toughening resin solution.
[0064] The polyester phosphate ester was prepared by the preparation example. The phosphorus-containing epoxy resin was DOPO-NQ type epoxy resin, the DCPD type epoxy resin was dicyclopentadiene-phenol epoxy resin, the cyanate ester resin was 10 parts of bisphenol A type cyanate ester and 5 parts of diphenylmethane diisocyanate, the molecular weight of the polyphenylene ether resin was 1000-3000, the linear phenolic resin was 6 parts of dicyclopentadiene type phenolic resin and 12 parts of phenolic type phenolic resin, the curing agent was dicyandiamide, the catalyst was 2-ethyl-4-methylimidazole, the filler was 12 parts of aluminum hydroxide and 20 parts of silica powder, and the solvent was 14 parts of cyclohexanone, 4 parts of acetone and 6 parts of toluene. The gelation time of the modified halogen-free toughening resin solution obtained in step S3 was 342 s.
[0065] (2) Preparation of prepreg:
[0066] The modified halogen-free toughening resin solution prepared in step (1) S3 is conveyed to the glue applicator, impregnated with electronic grade glass fiber cloth, and baked in an oven at 130-190°C to produce a semi-cured sheet with a resin content of 60% and a gel time of 130s.
[0067] (3) Preparation of copper clad laminate:
[0068] After the six semi-cured sheets prepared in step (2) are stacked, 35μm copper foil is applied to both sides. The sheets are then pressed in a vacuum press at a pressure of 0.5-4.5MPa and a temperature that is gradually increased from 120℃ to 210℃ for 2-3 hours to produce a modified halogen-free toughened copper clad laminate.
[0069] Comparative Example
[0070] A method for preparing a copper-clad laminate includes the following steps:
[0071] (1) Preparation of resin solution:
[0072] Add 40 parts of solvent, 45 parts of phosphorus-containing epoxy resin, 20 parts of DCPD type epoxy resin, then add 12 parts of linear phenolic resin, 0.8 parts of curing agent, 0.10 parts of catalyst, and 25 parts of filler. Stir for 2 hours, and then ball mill for 1 hour to obtain the desired resin solution.
[0073] Among them, the phosphorus-containing epoxy resin is DOPO type epoxy resin, the DCPD type epoxy resin is dicyclopentadiene-phenol epoxy resin, the linear phenolic resin is dicyclopentadiene-phenol epoxy resin, the curing agent is dicyandiamide, the catalyst is 2-methylimidazolium, the filler is 18 parts SiO2 and 7 parts aluminum hydroxide, and the solvent is 25 parts butanone and 15 parts propylene glycol monomethyl ether; the gelation time of the obtained resin solution is 354s.
[0074] (2) Preparation of prepreg:
[0075] The resin solution prepared in step (1) is conveyed to the glue applicator, impregnated with electronic grade glass fiber cloth, and baked in an oven at 130-190°C to produce a semi-cured sheet with a resin content of 55% and a gel time of 80s.
[0076] (3) Preparation of copper clad laminate:
[0077] After stacking the 6 semi-cured sheets prepared in step (2), 18μm copper foil is applied to both sides. The sheets are then pressed in a vacuum press at a pressure of 0.5-4.5MPa and a temperature that is gradually increased from 120℃ to 210℃ for 2-3 hours to produce a copper-clad laminate.
[0078] Test method description:
[0079] (1) Impact strength test (KJ / m) 2 GB / T2576-2021 Test Methods for Performance of Resin Cast-in-Place Bodies;
[0080] (2) Bending strength (MPa): GB / T 2568—1995, compression rate 10mm / min;
[0081] (3) Peel strength (N / mm): GB / T 4722-2017-7.2.1;
[0082] (4) Flame retardancy: GB / T 4722-2017-6.4.1;
[0083] (5)T288(min): GB / T 4722-2017-6.11;
[0084] (6) Glass transition temperature (DSC, °C): GB / T 40396-2021.
[0085] The test data for each embodiment and comparative example are shown in Table 1.
[0086] Table 1. Test data for each embodiment and comparative example.
[0087]
[0088] Comparing the test data in Table 1, it can be seen that compared with Comparative Example 1, Examples 1-3 show significant improvements in impact strength, peel strength, T288, and glass transition temperature. All examples achieve UL94-V0 flame retardancy, but in terms of specific burning time, Examples 1-3 exhibit a clear advantage in flame retardancy. The flexural strength of Examples 1-3 is slightly lower than that of the Comparative Example because, compared to the Comparative Example, Examples 1-3 incorporate flexible segments of polyester phosphate ester and long-chain molecules from the cyanate ester and PPO modified systems, thereby reducing the network crosslinking density of the epoxy resin while increasing chain length, molecular polarity, and branching degree, thus improving heat resistance and flexibility.
[0089] Therefore, it can be seen that the copper-clad laminate prepared by the modified halogen-free toughening resin liquid of the present invention has better flexibility, higher impact strength, peel strength, T288 and glass transition temperature, and competitive flame retardant effect compared with the existing copper-clad laminate.
[0090] It is understood that the present invention has been described through some embodiments, and those skilled in the art will recognize that various changes or equivalent substitutions can be made to these features and embodiments without departing from the spirit and scope of the invention. Furthermore, under the teachings of the present invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of the invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the protection scope of the present invention.
Claims
1. A modified halogen-free toughening resin adhesive, characterized in that, The product comprises the following components by weight: 12-18 parts of polyester phosphate ester, 40-55 parts of phosphorus-containing epoxy resin, 15-25 parts of dicyclopentadiene-type epoxy resin, 10-15 parts of cyanate ester resin, 6-12 parts of polyphenylene ether resin, 10-18 parts of linear phenolic resin, 0.5-2 parts of curing agent, 0.05-0.2 parts of catalyst, 20-32 parts of filler, and 32-48 parts of solvent.
2. The modified halogen-free toughening resin adhesive according to claim 1, characterized in that, The polyester phosphate ester is generated by reacting polyphosphoric acid and polyester polyol.
3. The modified halogen-free toughening resin adhesive according to claim 2, characterized in that, The polyphosphoric acid contains more than 85% P2O5, and the polyester polyol is selected from at least one of polyethylene adipate, 1,6-hexanediol adipate, trimethylolpropane adipate, and diethylene glycol adipate.
4. The modified halogen-free toughening resin adhesive according to claim 2, characterized in that, The preparation method of the polyester phosphate ester includes the following steps: under an inert gas atmosphere, 80-100 parts of polyester polyol are added first, and 3-5 parts of polyphosphoric acid are added while stirring. The temperature is raised to 100-110℃ and maintained for 3-4 hours. Then, after hydrolysis, washing and reflux to remove water, polyester phosphate ester is obtained.
5. The modified halogen-free toughening resin adhesive according to claim 1, characterized in that, The phosphorus-containing epoxy resin is selected from one or a mixture of any two or more of the following: DOPO type epoxy resin, DOPO-HQ type epoxy resin, and DOPO-NQ type epoxy resin.
6. The modified halogen-free toughening resin adhesive according to claim 1, characterized in that, The dicyclopentadiene-type epoxy resin is a dicyclopentadiene-phenol epoxy resin.
7. The modified halogen-free toughening resin adhesive according to claim 1, characterized in that, The cyanate resin is selected from one or a mixture of any two or more of the following: bisphenol A cyanate, bisphenol F cyanate, diphenylmethane diisocyanate, and dicyclohexylmethane diisocyanate.
8. The modified halogen-free toughening resin adhesive according to claim 1, characterized in that, The molecular weight of the polyphenylene ether resin is 1000~3000.
9. The modified halogen-free toughening resin adhesive according to claim 1, characterized in that, The linear phenolic resin is selected from one or a mixture of any two or more of the following: phenolic resin, bisphenol A resin, dicyclopentadiene resin, and aminotriazine resin.
10. The modified halogen-free toughening resin adhesive according to claim 1, characterized in that, The curing agent is selected from one or a mixture of any two or more of dicyandiamide, diaminodiphenylmethane, and diaminodiphenyl sulfone; the catalyst is 2-methylimidazole, 2-ethyl-4-methylimidazole, or 2-phenylimidazole; the filler is selected from a mixture of any two or more of talc, SiO2, TiO2, aluminum hydroxide, and alumina, and the particle size of the filler is 0.5~3 μm.
11. A method for preparing a modified halogen-free toughening resin adhesive as described in any one of claims 1 to 10, characterized in that, Includes the following steps: S1. Dissolve 6-12 parts of polyphenylene ether resin in 16-24 parts of solvent. After the solution is clear, add 10-15 parts of cyanate ester resin. While stirring, heat to 80℃-90℃, add 0.05-0.2 parts of catalyst and react for 0.8-1.2 hours. Stop heating, add another 16-24 parts of solvent, and cool to room temperature to obtain resin 1. S2. Take 12-18 parts of polyester phosphate, 40-55 parts of phosphorus-containing epoxy resin, and 15-25 parts of dicyclopentadiene epoxy resin. Stir and heat to 80℃-90℃, react for 0.8-1.2h, and then cool to room temperature to obtain resin 2. S3. Add resin 1 and resin 2 in sequence, then add 10-18 parts of linear phenolic resin, 0.5-2 parts of curing agent, and 20-32 parts of filler. Stir for 2 hours, and then ball mill for 1 hour to obtain modified halogen-free toughening resin solution.
12. The method for preparing the modified halogen-free toughening resin solution according to claim 11, characterized in that, The gelation time of the modified halogen-free toughening resin solution obtained in step S3 is 300~400s.
13. A method for preparing a modified halogen-free toughened copper clad laminate, characterized in that, Includes the following steps: (1) Preparation of resin solution: The modified halogen-free toughening resin solution is prepared by the method of preparation of modified halogen-free toughening resin solution as described in claim 11 or 12. (2) Preparation of semi-cured sheet: The modified halogen-free toughening resin liquid prepared in step (1) is transported to the glue applicator, impregnated with electronic grade glass fiber cloth, and baked in an oven at 130~190℃ to produce a semi-cured sheet with a resin content of 40%~60% and a gel time of 60~130s. (3) Preparation of copper clad laminate: After stacking two or more prepregs prepared in step (2), 18~35µm copper foil is applied to both sides. The laminate is then pressed in a vacuum press at a pressure of 0.5~4.5MPa and a temperature gradually increased from 120℃ to 210℃ for 2~3h to produce a modified halogen-free toughened copper clad laminate.
Citation Information
Patent Citations
Adhesive resin compositions, and laminates and flexible printed wiring boards using same
CN102333835A
Phosphorus-containing epoxy resin composition and prepreg and laminated board prepared by using phosphorus-containing epoxy resin composition
CN109535390A